Phenotypic and Genotypic Characterization of ESBL and AmpC β-Lactamase-Producing E. coli Isolates from Poultry in Northwestern Romania - Anca Rus; Iulia-Maria Bucur; Kalman Imre; Andreea Talida Tirziu; Andrei Alexandru Ivan; Radu Valentin Gros; Alex Cristian Moza; Sebastian Alexandru Popa; Alexandra Ban-Cucerzan; Emil Tirziu (Antibiotics, 2025)
Background/Objectives: The widespread use of antibiotics in animal husbandry has led to an increase in antimicrobial-resistant Escherichia coli, particularly strains producing extended-spectrum β-lactamases (ESBL) and AmpC β-lactamases. This study aimed to isolate and characterize such strains from fecal samples of broiler chickens (n = 71) and slaughtered turkeys (n = 31) in northwestern Romania. Methods: Antimicrobial susceptibility testing and PCR were used to evaluate phenotypic resistance patterns and detect the presence of resistance genes (AmpC, blaZ, and blaTEM). Results: The results showed that 55% of turkey and 61% of broiler isolates were presumptive ESBL/AmpC producers. Among all isolates, 50% were classified as extensively drug-resistant (XDR), 44% as multidrug-resistant (MDR), and only 6% were fully susceptible. Gene detection revealed an overall prevalence of 44.2% for AmpC, 72.7% for blaZ, and 58.1% for blaTEM, yielding a total penetrance of 51.09%. The diagnostic odds ratio (DOR) values, ranging from 0.67 to 81, suggest the efficacy of the antibiotic susceptibility testing method used in detecting the presence of these resistance genes. Conclusion: Overall, these findings highlight a significant burden of antimicrobial-resistant, poultry-associated E. coli strains, warranting stricter antimicrobial stewardship.